Availability and integration of health data on refugee and migrants in health information systems. (30th September 2020) - Bozorgmehr, K; Jahn, R; Biddle, L; Rohleder, S; Puthopparambil, S
Abstract: This presentation discusses the findings of a Health Evidence Network synthesis report on availability and integration of refugee and migrant health data in health information systems in the WHO European Region. Based on an analysis of 41 full-text studies and 696 abstracts, the report found that refugee and migrant health data were available in less than half of the Region's Member States, and that data availability and integration, data collection systems, as well as indicators on migration varied markedly between states. From these findings, the report derived key policy considerations regarding the strengthening and harmonization of migrant health data collection, as well as governance and monitoring of health information systems.